(untitled) (Homiletic, 2021)
Upon the unexpected arrival of COVID-19, preachers have been forced to preach online. Among many problems and challenges in performing online preaching, a grave one has been the lack of theological consideration given to these new practices: to date, not a single publication can be found in the market that is dedicated to online preaching. Given the paucity of theological reflection related to this emerging genre, this article develops a theology of online preaching—epitomized as the Word digitalized—that encompasses yet goes beyond the homiletical scope of the conventional Barthian threefold perception of the Word (i.e., incarnated, written, and proclaimed). In the theology of online preaching developed here, eight representative types of online preaching currently practiced by preachers are examined, each demonstrating the Word digitalized in creative and effective ways.